Medial tibial stress syndrome. Issue 2 (20th January 2011) - Batt, Mark E; Batt, Mark
Abstract : Lecture 9 Medial tibial stress syndrome (MTSS) is an enigmatic condition with confusing terminology, the term often being used interchangeably with shin splints. It is suggested that MTSS and shin splints be used as generic rather than diagnostic terms. On account of variable definitions, the reported incidence rate varies from 4 to 35% in military and athletic populations. Broadly, it represents exertional lower leg pain centred on the posteromedial tibial border and being diffuse/linear (greater than 5 cm) rather than focal. Presentations of acute shin splints should be regarded as bone stress injuries until proven otherwise and not treated as periostitis with anti-inflammatory modalities/drugs. Chronic presentations are more likely in females, those with a running history less than 5 years, increased body mass index, larger calf girth, increased hip rotation, standing foot pronation and a history of orthotics use, MTSS or stress fracture. Muscle hernia, stress fracture and chronic exertional compartment syndrome should be ruled out. The differential diagnosis also includes radiculopathy, nerve entrapment syndromes and the possibility of an accessory muscle should not be overlooked. There are few randomised controlled trials (RCTs) that have studied treatment and prevention and those available suggest that rest is probably as beneficial as any other form of intervention. Prevention may be afforded by either shock absorbing insoles or more formal orthotics. The pathophysiology would seem to be related to diffuse bone stress with resultant periostalgia. Thus rest and the possible use of compressive splints are advised with a graduated return to running activities once risk factors have been addressed.